AVALIAÇÃO DA QUALIDADE CONSTRUTIVA DE HABITAÇÕES DO PROGRAMA MINHA CASA MINHA VIDA EM JUIZ DE FORA: O CASO DO RESIDENCIAL MIGUEL MARINHO - Mendes, Matheus Pereira; Zambrano, Letícia Maria de Araújo; Bastos, Pedro Kopschitz Xavier (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The Brazilian governmental program My House My Life (MCMV) is the biggest action related to habitation in the country, which has already contracted more than 4 million homes, contributing to solve the housing deficit. The program has been using faster and more economical construction techniques, neglecting the impact of the solutions adopted on the building performance, which has resulted in a high number of constructive problems, reason for many complaints from the users. Therefore, this paper aims to present part of the results from an university extension program that evaluates the projects executed by the MCMV, located in the city of Juiz de Fora. Specifically, the study presents the results of the evaluation of constructive issues in one of the housing complex, presenting the methodology used for data collection, results and the analysis of these data. Although the dwellings were delivered five years ago, many problems were observed in several buildings of the studied range, mainly originated from the design and execution phases. Hopefully, this work may contribute to the elaboration of guidelines that allow the development of MCMV improvements and preventive techniques of constructive problems.